Similar responses of circulating microRNAs to acute high-intensity interval exercise and vigorous-intensity continuous exercise - Shu Fang eCui; Cheng eWang; Xin eYin; Dong eTian; Qiu Ju eLu; Chen Yu eZhang; Xi eChen; Ji Zheng eMa; Ji Zheng eMa (Frontiers in Physiology, 2016)
AbstractHigh-intensity interval exercise (HIIE) has been reported to be more beneficial for physical adaptation than low-to-moderate exercise intensity. Recently, it is becoming increasingly evident that circulating miRNAs (c-miRNAs) may distinguish between specific stress signals imposed by variations in the duration, modality, and type of exercise. The aim of this study is to investigate whether or not HIIE is superior to vigorous-intensity continuous exercise (VICE), which is contributing to develop effective fitness assessment. Twenty-six young males were enrolled, and plasma samples were collected prior to exercise and immediately after HIIE or distance-matched VICE. The miRNA level profiles in HIIE were initially determined using TaqMan Low Density Array (TLDA). And the differentially miRNAs levels were validated by stem-loop quantitative reverse-transcription PCR (RT-qPCR). Furthermore, these selective c-miRNAs were measured for VICE. Our results showed that some muscle-related miRNAs levels in the plasma, such as miR-1, miR-133a, miR-133b, and miR-206 significantly increased following HIIE or VICE compared to those at rest (P < 0.05), and there was only a significant reduction in miR-1 level for HIIE compared to VICE (P < 0.05), while no significant differences were observed for other muscle-related miRNAs between both exercises (P > 0.05). In addition, some tissue-related or unknown original miRNA levels, such as miR-485-5p, miR-509-5p, miR-517a, miR-518f, miR-520f, miR-522, miR-553, and miR-888, also significantly increased (P < 0.05) in both exercises compared to rest. However, no significant differences were found between both exercises (P > 0.05). Overall, endurance exercise assessed in this study both led to significant increases in selective c-miRNAs of comparable magnitude, suggesting that both types of endurance exercise have general stress processes. Accordingly, the similar responses to both acute exercises likely indicate both exercises can be used interchangeably. Further work is needed to reveal the functional significance and signaling mechanisms behind changes in c-miRNA turnover during exercise.